An approach to mitigating the premature death of the battery of sensor node - Chanagala, Satyanarayana; J.Khan, Z (International Journal of Engineering and Technology, 2018)
The prime objective of this paper is to investigate the impact of the sampling interval, which is one of the sensor node parameters, on the battery life of sensor node. An improper selection of sampling interval will lead to pronounced recovery effect which leads to premature death of the battery of sensor node. The suggested approach used in this work has achieved a significant lifetime improvement of the battery of sensor node.